Food Fermentation as a Virtual Laboratory Learning Media to Empower Student’s Science Process Skills - Wachida Maftuhatun Nisa; Umi Fatmawati; Slamet Santosa (Postgraduate, University of Mataram, 2023)
The purposes of this research are to produce a discovery learning-based virtual laboratory learning media, to assay the feasibility of the media, and to test students' science process skills before and after the implementation of developed media. Â The research method used is a Research and Development (R&D) with a 4D (Four-D Model) which was modified into 3D (Define, Design, and Develop). The validation stage was carried out by a media expert, content expert, and learning expert. The instruments used include questionnaires for the analysis of student needs, interview questionnaires, validator instruments, student responses, teacher responses, and pretest-posttest. The data collection technique was carried out by distributing student and teacher response questionnaires after learning. Science process skills are measured using a pretest-posttest. The virtual-laboratory learning media can be operated on android and personal computers (PC). The validation results showed that the multimedia was very feasible with a percentage of 92.7%, meanwhile, the material, and evaluation validation were considered feasible, with a percentage of 85.1% and 83.02% respectively. There were differences in students' science process skills before and after the implementation of discovery learning-based virtual laboratory learning media shown by the results of the paired t-test, namely the Sig value (2-tailed) 0.000<0.05